Genetics and Anthropology - San Martín, Mauricio (1955)
Every living being without exception, whether animal or vegetable, belongs to a species only include their hereditary potentials in a given environment, potentials that come into play in the differentiation of all psychic external and internal physical characteristics, suncionales and of an individual or phenotype.